Current Health Status and Care Practices among the Retired Elderly Professors of Tribhuvan University - G.C., Bishnu (Tribhuvan University Journal, 2018)
This study tries to find out the current health status and the care practices of the retired elderly Professors of Kathmandu. Descriptive research design has been followed and all together 30 male and 10 female retired professors were selected conveniently. Structured questionnaire was used to collect the data and information. This study reveals that, most of the respondents (around 50%) were from 60-69 years young-old age group. In most cases, economic condition (around 90% have their own pension), marital life (around 62.5% are currently married) and family support (more than 90%) of the respondents were satisfactory about their current health status. Their physical health seems good but they were still suffering from the backache (100%), poor eye sight (80%), pain around the waist (60%), gastritis (60%) and headache (40%) which was often in elderly age due to auto immune and wear and tear theory. It was found that some of them were suffering from different chronic and acute diseases but they were cared and supported by their family members in their hard time. They had practiced regular medical checkups due to satisfactory family life and economic status.